The perception of the production costs of the organic banan in Cantón Machala, Ecuador - Rivera León, Félix Armando (2018)
The present study is aimed at analyzing the perception of indirect manufacturing costs as one of the relevant nodes in organic banana production in Canton Machala companies in Ecuador. Different theoretical methods such as analysis and synthesis and modeling are used to achieve the objective. As an empirical method, a survey was applied to a sample of 66 organic banana companies, which was processed through the statistical package SPSS 23.0. The main results are that in organic banana companies the perception of costs is examined from three key moments of the production process: before, during, after production, and at the same time provides an analysis approach that improves the aggregation management of the costs of production in an environmental environment.